Comparison of optimum conditions when extracting PHAs from different waste sludge sources - Lu, Meng-Shan; Lai, Long-Li; Tsai, Yung-Pin (Journal of Environmental Engineering and Landscape Management, 2018)
Biological wastewater treatment plants produce great amounts of sludge daily. It is a very big loading (cost) for treating the waste sludge. Polyhydroxyalkanoates are a family of polyhydroxyesters. The technologies of extracting PHAs from wasted sewage sludges of municipal wastewater, fermentation industry and husbandry were developed in the study. In the NaOCl/SDS extraction technology, the concentration of NaOCl and liquid-solid ratio are two essential factors directly influencing extraction efficiency. The experimental results verified under the optimal conditions for extracting PHAs, the content of recovered PHAs was 44.2±0.89 mgPHA/gVSS and the purity of recovered PHAs was >99.5 wt% for the waste sludge from municipal wastewater treatment plants. For fermentation industry sludge, under the adequate extraction conditions for PHAs recovery, the content and purity of recovered PHAs were 18.8±0.66 mgPHA/gVSS and 50.6±6.83 wt%, respectively. For husbandry sludge, the content and purity of recovered PHAs were 33.7±0.16 mgPHA/gVSS and 76.7±5.2 wt%, respectively.